The role of mycelium production and a MAPK-mediated immune response in the C. elegans-Fusarium model system - Muhammed, Maged (2012)
Fusariosis is an emerging infectious complication of immune deficiency, but models to study this infection are lacking. The use of the soil nematode Caenorhabditis elegans as a model host to study the pathogenesis of Fusarium spp. was investigated. We observed that Fusarium conidia consumed by C. elegans can cause a lethal infection and result in more than 90% killing of the host within 120 hours, and the nematode had a significantly longer survival when challenged with Fusarium proliferatum compared to other species. Interestingly, mycelium production appears to be a major contributor in nematode killing in this model system, and C. elegans mutant strains with the immune response genes, tir-1 (encoding a protein containing a TIR domain that functions upstream of PMK-1) and pmk-1 (the homolog of the mammalian p38 MAPK) lived significantly shorter when challenged with Fusarium compared to the wild type strain. Furthermore, we used the C. elegans model to assess the efficacy and toxicity of various compounds against Fusarium. We demonstrated that amphotericin B, voriconazole, mancozeb, and phenyl mercury acetate significantly prolonged the survival of Fusarium-infected C. elegans, although mancozeb was toxic at higher concentrations. In conclusion, we describe a new model system for the study of Fusarium pathogenesis and evolutionarily preserved host responses to this important fungal pathogen.